Exploring the use of conversational agents in healthcare: an overview, conceptual analysis and case study - Dhinagaran, Dhakshenya Ardhithy (Nanyang Technological University, 2022)
Conversational agents (CAs) or chatbots are computer programs designed to participate in human-like conversations with their users. The growing interest in these agents is evident in their employment in numerous fields including business, retail, and even healthcare. The need for new initiatives to promote healthy living is apparent in Singapore given its highly stressful and fast-paced way of life, insufficient time for physical activity, and frequent dining out. Singapore is technologically astute and always on the lookout for novel initiatives, such as the use of CAs, to improve patient care and support healthcare staff.